Trend and factors associated with non-suppression of viral load among adolescents on ART in Tanzania: 2018–2021 - Quaker, Andrewleon S.; Shirima, Laura J.; Msuya, Sia E. (Frontiers in Reproductive Health, 2024)
Background: Tanzania is one of the countries with a high burden of HIV. It has an estimated 1.4 million people living with HIV in 2021. Adolescents living with HIV on antiretroviral therapy (ART) have worse treatment adherence, viral suppression, and mortality rates compared to adults. This study aim was to determine the trend of non-suppression among adolescents on ART in Tanzania from 2018 to 2021 and latest associated predictors. Methodology: The study utilized data of adolescents (10-19 years) receiving ART in Tanzania mainland for the period of 2018-2021 from the National Care and Treatment Centers database. The primary outcome of interest was non-suppression of viral load, defined as a VL above 1000 copies/mL. The study employed multivariable logistic regression models to identify factors associated with non-suppression of VL. STATA 15 statistical software was used to analyze the data. Results: Records of 65,942 adolescents present in the CTC database Tanzania were analyzed. Approximately more than half were female 38,544 (58.5%). The proportion of non-suppression was 34.5%, 23.3%, 12.1%, and 9.7% for the years 2018 to 2021, respectively. After adjusting for other factors, adolescents with a history of poor adherence to ART in the last six months had higher odds of non-suppression (OR=1.95, 95% CI=1.64, 2.31). Adolescents on second or third line ART regimens were almost two times more likely to be non-suppressed compared to those on first-line regimens (OR=2.85, 95% CI=2.52, 3.23). Girls had lower odds of non-suppression compared to boys (OR=0.91, 95% CI=0.84, 0.98), and patients attending hospitals compared to those attending dispensaries (OR=0.79, 95% CI=0.72, 0.87). Conclusion: Being female, having good history of adherence over the last six months, and attending hospital level was significantly associated with lower levels of non-suppression, while being on second line ART or attending lower health facilities increased the odds of non-suppression. Efforts to enhance the quality and capacity of health services at lower-level facilities (dispensaries and health centers) should be prioritized, as well as promoting gender-sensitive approaches that take into account the unique needs and experiences of adolescent girls and boys are needed to improve VL suppression among this population.